Development of PPKn learning module based on Surabaya local wisdom to improve student's learning achievement on social cultural diversity materials in Class IV at SDN Kandangan I/121 Surabaya - Sutrisno Sutrisno; Sarmini Sarmini; Nanik Setyowati (Lighthouse Publishing, 2021)
This study aims to (1) produce a Civics learning module based on local wisdom in Surabaya to improve student achievement in fourth-grade elementary school; (2) describe the validity, practicality, and effectiveness of the Civics learning module based on local wisdom in Surabaya to improve learning achievement in the material